2011
DOI: 10.1037/a0025189
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness is associated with fewer PTSD symptoms, depressive symptoms, physical symptoms, and alcohol problems in urban firefighters.

Abstract: Mindfulness may be important to consider and include in models of stress, coping, and resilience in firefighters. Future studies should examine the prospective relationship between mindfulness and health in firefighters and others in high-stress occupations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
169
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 29 publications
11
169
1
7
Order By: Relevance
“…For example, self-reported dispositional mindfulness has been found to be inversely associated with PTSD symptoms in college students (Thompson et al, 2011). In addition, many researchers found that dispositional mindfulness was a predictive factor of mental health problems (Boden et al, 2012; Boughner, Thornley, Kharlas, & Frewen, 2016; Hagen, Lien, Hauff, & Heir, 2016; Smith et al, 2011; Thompson & Waltz, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…For example, self-reported dispositional mindfulness has been found to be inversely associated with PTSD symptoms in college students (Thompson et al, 2011). In addition, many researchers found that dispositional mindfulness was a predictive factor of mental health problems (Boden et al, 2012; Boughner, Thornley, Kharlas, & Frewen, 2016; Hagen, Lien, Hauff, & Heir, 2016; Smith et al, 2011; Thompson & Waltz, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that an individual's ability to be mindful is predictive of PTSD symptoms; in a study of 124 urban firefighters increased mindfulness was associated with fewer symptoms of PTSD, and lower levels of depression (Smith et al, 2011). In particular the mindful concept of non-judgment of experience has been shown to account for a unique proportion of the variance in PTSD avoidance symptoms (Thomson & Waltz, 2010).…”
Section: Mindfulness and Ptsdmentioning
confidence: 99%
“…[46][47][48][49][50][51][52] Indeed, it has been suggested that pretraumatic mindful tendencies promote acceptance and awareness of posttraumatic responses, thereby reducing avoidance, re-experiencing and hyperarousal reactions to trauma-related stimuli and preventing the onset of PTSD. 38 In particular, facets of mindfulness, including describing (the ability to label or note observed phenomena, such as emotions), acting with awareness and nonjudgment, mediate the association between childhood and lifetime trauma exposure and the risk for posttraumatic symptoms.…”
Section: Theoretical Basis Of Mindfulness-based Treatment Approaches mentioning
confidence: 99%